2017
DOI: 10.1088/1361-6498/aa80a4
|View full text |Cite
|
Sign up to set email alerts
|

Removal of scatter radiation in paediatric cardiac catheterisation: a randomised controlled clinical trial

Abstract: Radiation doses received during paediatric cardiac catheterisation procedures resulted in a significant increase in DNA damage while maintaining acceptable image quality and diagnostic efficacy. It is feasible to remove the anti-scatter grid resulting in a reduction in DNA damage to the patient. The γH2AX assay may be used for assessment of dose optimisation strategies in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…However, their results were not stratified by patient size and their baseline comparison involved the use of an anti-scatter grid in all patients including those <20 kg. 16 Our study demonstrated similar dose reductions when comparing AGT to standard imaging with an anti-scatter grid in place…”
Section: Discussionsupporting
confidence: 62%
“…However, their results were not stratified by patient size and their baseline comparison involved the use of an anti-scatter grid in all patients including those <20 kg. 16 Our study demonstrated similar dose reductions when comparing AGT to standard imaging with an anti-scatter grid in place…”
Section: Discussionsupporting
confidence: 62%
“…Roy et al [26] reported a 47% reduction in radiation dose to the patient as well as reduced scatter to the operator with removal of the grid during coronary angiography. In pediatric cardiac catheterization, Gould et al [27] reported a 30% decrease in DNA double-strand breakages with grid removal. Fritz et al [28] also found that the benefit of the antiscatter grid in pediatric abdominal radiographs decreases in smaller patients and proposed not using it in certain situations.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric cardiac catheterization, Gould et al . [27] reported a 30% decrease in DNA double-strand breakages with grid removal. Fritz et al .…”
Section: Discussionmentioning
confidence: 99%